Using RTI in secondary schools : a training manual for successful implementation - Callender, Wayne A. (Corwin, a SAGE Company, 2014)
No educator wants to see their secondary students fail classes, drop out, and risk a lifetime of reduced opportunity. Response to Intervention (RTI) allows educators to identify at-risk students and help them before problems snowball. Developed specifically for secondary schools, this comprehensive manual offers a step-by-step RTI program, including helpful templates and tools. Readers will learn how to: Combine two leading, research-based RTI approaches (Standard Protocol and Problem-Solving) to make the most of existing resources Develop and manage a universal screening process that identifies at-risk students Create a comprehensive student intervention plan (iPlan) for each student, with a focus on skill-building Understand and implement curriculum-based measurement and other progress monitoring techniques Adapt RTI to Special Education programs Learn how to plan, deliver, and maintain a successful RTI program!